2009
DOI: 10.1136/oem.2008.041772
|View full text |Cite
|
Sign up to set email alerts
|

Maternal occupational exposure to solvents and congenital malformations: a prospective study in the general population

Abstract: Objective: To study the relations between maternal occupational exposure to solvents during pregnancy and the risk of congenital malformations. Methods: A prospective population-based cohort, specifically designed to study the impact of maternal exposure to solvents on the risk of congenital malformations, began in 2002 in three districts of Brittany (France). 3421 pregnant women were recruited until the end of 2005 by physicians before 19 weeks of gestation and followed through birth. Information on pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
74
4
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 37 publications
4
74
4
8
Order By: Relevance
“…However, low maternal education showed a significant association with congenital malformations and BOH [24,25]. Maternal occupation has been implicated in the incidence of congenital malformations [26]. However, maternal occupation did not confer risk in Group 1 and Group 2 similar to other studies [25,27].…”
Section: Discussionsupporting
confidence: 37%
“…However, low maternal education showed a significant association with congenital malformations and BOH [24,25]. Maternal occupation has been implicated in the incidence of congenital malformations [26]. However, maternal occupation did not confer risk in Group 1 and Group 2 similar to other studies [25,27].…”
Section: Discussionsupporting
confidence: 37%
“…Occupational exposures and activities are increasingly linked to adverse reproductive outcomes in working populations (1)(2)(3)(4)(5)(6)(7)(8). Occupational exposures associated with adverse reproductive outcomes include increased risks for spontaneous miscarriages among (i) healthcare workers exposed to chemicals including disinfectants, antineoplastic, and anesthetic drugs and (ii) women in industry exposed to heavy metals and solvents (9).…”
mentioning
confidence: 99%
“…To our knowledge, this is the first study where the risk of congenital malformations in relation to occupational painting has been investigated by a register-based approach. Some previous studies have focused on maternal exposure to volatile organic compounds (VOC) and have shown an increased risk of congenital anomalies among the children (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%